Performance analysis of gain ratio power allocation strategies for non-orthogonal multiple access in indoor visible light communication networks - Siyu Tao; Hongyi Yu; Qing Li; Yanqun Tang (EURASIP Journal on Wireless Communications and Networking, 2018)
Abstract Non-orthogonal multiple access (NOMA) is a promising method for enhancing the throughput in visible light communication (VLC) networks. In NOMA, signal power domain control, called gain ratio power allocation (GRPA), can significantly improve the user sum rate with full-time frequency resource utilization. In indoor NOMA-VLC networks, the scenario in which users are covered by VLC illuminants on the ceiling is typical. First, this paper proposes a novel GRPA strategy for a single VLC cell. Second, due to the difficulty of direct comparisons between our and previously reported GRPA strategies, this paper presents an alternative lower bound for comparability. Third, in two- and three- user cases, this paper analytically demonstrates that our NOMA-VLC GRPA strategy outperforms the aforementioned strategy, when successive interference cancellation (SIC) is used. Moreover, in the multi-user case, experimental results show that the average user data rate (AUDR) of multi-user cases under our strategy is better than that under the previous strategy. Finally, our paper provides both analytic and numerical results to prove that VLC single-cell system throughput under our strategy is better than that under the previous strategy. The proposed alternative lower bound is also proved to fit the original NOMA-VLC GRPA target asymptotically based on indoor VLC channels. Furthermore, to achieve the same AUDR, our strategy supports worse received conditions than does the previous strategy.